2015
DOI: 10.1523/jneurosci.3967-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Model of Chromosome 15q13.3 Microdeletion Syndrome Demonstrates Features Related to Autism Spectrum Disorder

Abstract: The chromosome 15q13.3 microdeletion is a pathogenic copy number variation conferring epilepsy, intellectual disability, schizophrenia, and autism spectrum disorder (ASD). We generated mice carrying a deletion of 1.2 Mb homologous to the 15q13.3 microdeletion in human patients. Here, we report that mice with a heterozygous deletion on a C57BL/6 background (D/ϩ mice) demonstrated phenotypes including enlarged/heavier brains (macrocephaly) with enlarged lateral ventricles, decreased social interactions, increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 67 publications
3
42
0
Order By: Relevance
“…Reduced AEP response in Df(h15q13)/+ mice has previously been shown in a similar paradigm with EEG measurements (Fejgin et al 2014, Kogan et al 2015, and we found that this difference is also present at the level of single cell responses. When averaging the evoked responses of all recorded cells in A1 in terms of increase in firing rate from baseline average rate, a reduced response amplitude was observed in the Df(h15q13)/+ mice.…”
Section: Neuronal Responses In the Auditory Paired Pulse Testing Parasupporting
confidence: 89%
See 3 more Smart Citations
“…Reduced AEP response in Df(h15q13)/+ mice has previously been shown in a similar paradigm with EEG measurements (Fejgin et al 2014, Kogan et al 2015, and we found that this difference is also present at the level of single cell responses. When averaging the evoked responses of all recorded cells in A1 in terms of increase in firing rate from baseline average rate, a reduced response amplitude was observed in the Df(h15q13)/+ mice.…”
Section: Neuronal Responses In the Auditory Paired Pulse Testing Parasupporting
confidence: 89%
“…Recently, encephalography (EEG) recordings in a mouse model of the 15q13.3 microdeletion syndrome, Df(h15q13)/+ mice, have been published (Fejgin et al 2014), and the mice display reduced excitability and reduced capacity to generate cortical evoked gamma oscillations. This finding has been reproduced in an independent 15q13.3 deletion mouse line (Kogan et al 2015). A possible cause for reduced cortical gamma oscillations is dysfunctional local cortical networks.…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…A recently developed heterozygous deletion D/+ mouse model with a homologous microdeletion has enlarged brains and lateral ventricles in adulthood [204]; enlarged head size has been observed in subjects with the microdeletion [272]. Although neuron number and dendritic morphology were not quantified in the D/+ mice, no gross differences were observed [204]. …”
Section: Lessons From Animal Modelsmentioning
confidence: 99%